IMMU-48. RATIONAL DEVELOPMENT AND CHARACTERIZATION OF MULTIVALENT TARGETING TANDEM AND PARALLEL CAR T CELLS FOR GLIOMA. (11th November 2019) - Yin, Yibo; Thokala, Radhika; Zhang, Logan; Kainth, Devneet; Haddad, Leila; Binder, Zev; Lin, Zhiguo; O'Rourke, Donald
Abstract: High grade glioma is the most common malignant primary brain tumor. Despite the best available therapy, the median survival is limited. Chimeric antigen receptor (CAR)-T cells effectively attack target positive tumor cells, demonstrating a promising possible treatment. Based on our previous clinical and pre-clinical studies, we utilized epidermal growth factor receptor variant III (EGFRvIII) and interleukin 13 receptor subunit alpha 2 (IL13Rα2) targeting single-chain variable fragments (scFvs) to generate bi-specific tandem CAR T cells and bi-specific parallel CAR T cells to decrease the potential of antigen escape and tumor recurrence. 5, 10, 15 or 20 flexible amino acids were utilized to link scFvs in tandem CARs. Ribosomal "skipping" 2A peptides were utilized to generate parallel CAR T cells. Flow-based IL13Rα2 staining on glioma stem cells (GSCs) showed 7 out 11 cases positive (64%) heterogeneous intratumoral expression. Tandem CAR T cells and parallel CAR T cells upregulated CD69 expression (P< 0.0001), generated IFNγ, interleukin 2 and TNFα (P< 0.0001), as well as exhibiting cytotoxic activity (P< 0.0001) when compared against un-transduced T cells, in co-culture with either single- or double-target positive GSCs. There was no significant difference between different lengths of linker in tandem CAR T cells. Parallel CAR T cells generated a larger cytokine response (P< 0.0001) and more effectively killed target positive cells (P< 0.05) than tandem CAR T cells. In summary, glioma associated target expression is heterogeneous in GSCs. Multivalent tandem CAR T cells and parallel CAR T cells effectively respond to target expressing tumor cells. The function of tandem CAR T cells is not relative with the length of linker. Parallel CAR T cells are a more promising strategy in generating gene modified multivalent targeting T cells.